Composição tecidual de carcaças e dos cortes comerciais de cordeiros com diferentes genotipos e rações - Leonardo de Rago Nery Alves (2012)
In order to evaluate the effects of different genotypes and diets over the carcass tissue composition, as well as the retail cuts of lambs, an experiment was conducted at the Model Farm of Pedro Leopoldo (field research) and in the laboratory of Animal Calorimetry and Metabolism, both connected to the Veterinary Medicine School at the Federal University of Minas Gerais. Among the 80 lambs used, 20 belonged each from a genotype proposed as follows: ½ Dorper x ½ Santa Inês (DSI), ½ Texel x ½ Sana Inês (TSI), Somalis x ½ Santa Inês (SSI) and Santa Inês (SI). Each genotype was divided in groups corresponding to each of the diets containing different fibrous sources evaluated: cane bagasse (CB), alfalfa hay (AH), citrus pulp (CP), soybean hulls (SH); so as to distribute them in in a completely randomized design in factorial scheme 4 x 4 (considering four genotypes and four diets). When they were slaughtered, the animals weighed about 35 kg. Their carcass was sectioned so that half of it could provide retail cuts such as neck, shoulder, ribs, racks, breast, loin and leg. They were subject to physical dissection in bones, muscles, fat and other tissues. From the leg, the muscularity rate of the carcass (MRC) was calculated. In general, the SSI animals presented lower yield of bones on the carcass and more fat yield. Besides, no difference in the muscular and other tissues yield was noticed. The AH diet favored the fat deposition by this genotype. The CP diet decreased the yield of the edible portion in the genotype DSI. The SI group presented the worst ratio muscle: bone (2,61) and the animals that were fed AH had this ratio favored. The AH diet favored the fat deposition by SSI favoring the highest average in the ratio fat: bone (1,55) and in the ratio muscle + fat: bone (4,81). The DSI animals presented higher MRC (0,424); and the animals that ingested CB presented higher MRC (0,412).The SI (genotype) presented higher weight (1378,67g), a tissue proportion similar to the other genotypes; and the different diets did not have any influence on this cut. The TSI animals and the CP presented higher total weight of the shoulder (1508,9 g and 1504,1 g); yet, the mentioned diets did not affect the tissue composition of the cut. The shoulder weight presented positive and high correlation to the muscle yield when compared to the weight of the empty body (r=0,55%). DSI animals fed AH obtained higher total average weight in the rib cut (1205,2 g) and the highest proportion of muscles (4,9%); as for the SSI fed AH, they presented the highest fat percentage. The rib fat is correlationed in a positive and high way to the fat yield in relation to the weight of the empty body (r=0,66%). The DSI animals presented higher muscle percentage on the rib muscle (48,57%). As for the SSI, they presented the highest fat percentage (23,76%) and the lowest percentage of bones (21,61%).The breast cut did not present any significant difference for the treatments. The DSI genotype presented higher average of muscular proportion on the loin cut (54,17%) and the SSI presented the higher proportion of fat, when fed AH (28,23%). TSI animals presented higher total weight of leg cut (2662,3 g). DSI animals that were fed SH obtained higher average percentage of bones (20,99%) and the SSI presented the higher fat proportion (17,39%) on this cut. It was concluded that both the fibrous sources and the genotype chosen for the diet change the body composition of lambs.